A Review of Virology: Molecular Biology and PathogenesisReview of: Virology: Molecular Biology and Pathogenesis, 1st ed.; Leonard C. Norkin; (2010). ASM Press, Washington DC. Hardcover, 725 pages. ISBN-10: 1555814530. - Susan Godfrey (American Society for Microbiology, 2011)
Review of: Virology: Molecular Biology and Pathogenesis, 1st ed.; Leonard C. Norkin; (2010). ASM Press, Washington DC. Hardcover, 725 pages. ISBN-10: 1555814530.